Feasibility study of vannamei shrimp (Litopenaeus vannamei) farming in Bantan subdistrict, Bengkalis Regency, Riau Province - Prasetia, Eko; Tang, Usman Muhammad; Prianto, Eko (Universitas Teuku Umar, 2025)
The development of Whiteleg shrimp (Litopenaeus vannamei) aquaculture in Bantan Subdistrict, Bengkalis Regency, requires a comprehensive feasibility study due to challenges such as low salinity and the distance of ponds from the sea. This study aims to assess the feasibility of pond development from water quality, ecological carrying capacity, social, and economic perspectives. The research utilized a survey and case study approach, with data collected through field observations, in situ measurements, interviews, and documentation. Data analysis included land suitability scoring, carrying capacity estimation, and financial evaluations using R/C Ratio, NPV, B/C Ratio, IRR, and Payback Period. Results indicate that most locations fall into the “suitable” to “highly suitable” categories based on water quality and environmental parameters. The carrying capacity analysis shows that the area can support shrimp farming activities without degrading the ecosystem, consistent with findings in other low-salinity regions where adaptive management is applied. Furthermore, local government support through coastal zoning regulations and sustainable programs is found to be critical for long-term success. Economic analysis demonstrates financial feasibility, evidenced by an R/C Ratio greater than 1, a positive NPV, and an IRR exceeding the prevailing interest rate. Socially, the community supports shrimp pond development due to its positive impact on income and employment, although issues regarding land ownership and potential conflicts between farmers and fishers require careful management. In conclusion, vannamei shrimp farming in Bantan Subdistrict is feasible for sustainable development, provided that environmental conservation, economic risk mitigation, and inclusive stakeholder participation are properly addressed.